Reconstruction following Excision of Malignant Scalp Tumors with Split Thickness Skin Graft with and without Acellular Dermal Matrix: A Comparative Study - Rahmati, Javad (J Cutan Aesthet Surg, 2019)
BACKGROUND: Basal cell carcinoma (BCC) and squamous cell carcinoma (SCC) are the most common malignancies, which occur on the scalp. There are various therapeutic methods for managing these malignancies in which the standard treatment method of both is surgical excision with a good margin. Sometimes, the patients need full-thickness excision due to the deep invasion, so exposing the underlying calvarium may be a challenge for surgeons. OBJECTIVES: We evaluated the outcomes of using the combined therapy of acellular dermal matrix and split-thickness skin graft (STSG) in comparison with using only STSG in the treatment of defects caused by the excision of scalp malignant tumors among the patients who attended Imam Khomeini Hospital Complex and Razi Hospital of Tehran, Iran. We also evaluated the satisfaction of both surgeons and patients among these two methods of treatment. MATERIALS AND METHODS: All the candidates were divided into the two groups, that is, of case and control, randomly. The case group underwent the treatment using acellular dermal matrix and STSG, whereas the control group underwent the treatment by only STSG on the wound. In both groups, BCC and SCC were excised with a margin of 6 and 10 mm, respectively, on the skull bone. Then, a layer of bone was removed by osteotomy in order to reach the bleeding points. All patients were followed up for 7, 30, and 90 days after the surgery, and the results were recorded. RESULTS: A significant difference in Manchester Scar Scale, wound contour formation, the mobility of the repair site, and patients and surgeon satisfaction was observed among both groups based on visual analog scale. We found better outcomes in the case group, especially in wound contour formation during 90 days of follow-up. However, the satisfaction of both surgeons and patients was achieved in the case group. Satisfaction of surgeons was achieved in the case group with a relative superiority to the control group according to the Manchester Scar Scale.